2017
DOI: 10.24130/eccd-jecs.196720171114
|View full text |Cite
|
Sign up to set email alerts
|

Okul öncesi dönem çocuklarının ebeveynlerinin akıllı sembol kullanımı ve televizyondan koruma yöntemleri

Abstract: Bu çalışmanın amacı 3-6 yaş arası çocuğu olan annelerin akıllı sembolleri bilme ve kullanma düzeyleri ile çocuklarını televizyonun zararlı etkilerinden nasıl koruduklarını tespit etmektir. Araştırmanın nicel bölümü 3-6 yaş arasında çocuğu olan 130 annenin katılımıyla oluşturulmuştur. Nitel bölümde ise 8 anneden elde edilen veriler dikkate alınmıştır. Nicel ve nitel yöntemler kullanılan bu çalışmada katılımcılara anket ve yarı yapılandırılmış görüşme formu uygulanmıştır. Nicel verilerin değerlendirilmesinde ANO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Moreover, the children's aggressive behaviors were observed to be decreasing. In the study conducted by Banko, İlhan and Şallı (2017), the use of smart symbols on television by families and their methods of protecting children from harmful effects of television were examined. At the end of the study, the mothers' use of smart symbols was found to be high.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the children's aggressive behaviors were observed to be decreasing. In the study conducted by Banko, İlhan and Şallı (2017), the use of smart symbols on television by families and their methods of protecting children from harmful effects of television were examined. At the end of the study, the mothers' use of smart symbols was found to be high.…”
Section: Introductionmentioning
confidence: 99%